Effectiveness of biomechanically stable pergola-like additively manufactured scaffold for extraskeletal vertical bone augmentation - Yang, Wei; Wang, Chao; Luo, Wenping; Apicella, Antonio; Ji, Ping; Wang, Gong; Liu, Bingshan; Fan, Yubo (Frontiers in Bioengineering and Biotechnology, 2023)
Extraskeletal vertical bone augmentation in oral implant surgery requires extra-osseous regeneration beyond the anatomical contour of the alveolar bone. It is necessary to find a better technical/clinical solution to solve the dilemma of vertical bone augmentation. 3D-printed scaffolds are all oriented to general bone defect repair, but special bone augmentation design still needs improvement. This study aimed to develop a structural pergola-like scaffold to be loaded with bone morphogenetic protein 9 (BMP9), vascular endothelial growth factor (VEGF) and stem cells from the apical papilla (SCAPs) to verify its bone augmentation ability even under insufficient blood flow supply. Scaffold biomechanical and fluid flow optimization design by finite element analysis (FEA) and computational fluid dynamics (CFD) was performed on pergola-like additive-manufactured scaffolds with various porosity and pore size distributions. The scaffold geometrical configuration showing better biomechanical and fluid dynamics properties was chosen to 3D-print and co-culture for 2 months, in vitro and subcutaneously into nude mice, with different SCAPs, BMP9 and VEGF combinations. Micro-CT and histological analysis of the explanted scaffolds showed new bone formation in the "Scaffold+SCAPs+BMP9" and the "Scaffold+SCAPs+BMP9+VEGF" groups where the VEGF addition did not significantly improve osteogenesis. No new bone formation was observed either for the "Blank Scaffold" and the "Scaffold+SCAPs+GFP" group. The results of this study indicate that BMP9 can effectively promote the osteogenic differentiation of SCAPs. The pergola-like scaffold can be used as an effective carrier and support device for new bone regeneration and mineralization in bone tissue engineering,and can play a crucial role in obtaining considerable vertical bone augmentation even under poor blood supply.